SOSIALISASI PENGENALAN RANSOMWARE SEBAGAI PENINGKATAN KEAMANAN DATA SISWA DI SMK PANTI KARYA - Ade Napila; Andrian Hidayat (Abdi Jurnal Publikasi, 2025)
In the digital era, data security is a major concern, especially in the education sector which stores sensitive information about students and institutions. One of the biggest threats to data security is ransomware attacks, a type of malware that encrypts the victim's data and demands a ransom payment for recovery. These attacks have become a serious threat to schools and educational institutions due to weak security systems and lack of user awareness of cyber threats. This service aims to introduce the concept of ransomware, analyze its impact on student data security, and identify effective steps to prevent such attacks in educational environments. The socialization methods used include literature studies, analysis of ransomware attack cases on educational institutions, and prevention strategies that can be implemented by schools and educators. The results of the study show that ransomware can cause data loss, operational disruption, and significant financial losses for educational institutions. Therefore, increasing awareness and education about cybersecurity is a very important step. In addition, implementing preventive measures such as regular data backups, using up-to-date security software, and training educators and students on good digital security practices can help reduce the risk of ransomware attacks. With this service, it is hoped that SMK Panti Karya will be more prepared in facing ransomware threats and be able to implement better security strategies to protect student data.